SISTEM INFORMASI POLIKLINIK TERPADU - Syahrial Syahrial (Jurnal Ilmu Komputer (JUIK), 2021)
Polyclinic management is currently using a computerized system. However, the existing system is almost entirely made separate or in the form of a stand-alone system. Management of clinical data, financial data, dispensary data and queuing data are used with different systems. Based on previous studies there has been a clinical information system, medical records, and inpatient / outpatient care, but the application is still independent. There are many references to previous studies that only manage clinical data, in this case medical records and pharmacy data. Financial management has never been integrated into the same system, especially for the polyclinic information system. The solution provided by researchers is by designing and building a system that combines clinical data management, care data, financial data, pharmacy data, and queuing data in one integrated system. System development utilizes web technologies such as PHP, HTML5, CSS, and Javascript programming languages. Data storage is designed using the MySQL database server. The use of web technology allows the system to run lightly and can be accessed both intranet and internet.